Chemical basis for alteration of an intraocular lens using a femtosecond laser - Bille, Josef F.; Engelhardt, Johann; Volpp, Hans-Robert; Laghouissa, Abdelmoutalib; Motzkus, Marcus (Biomedical optics express, 2017)
The chemical basis for the alteration of the refractive properties of an intraocular lens with a femtosecond laser was investigated. Three different microscope setups have been used for the study: Laser Induced Fluorescence (LIF) microscopy, Raman microscopy and coherent anti-Stokes Raman Scattering (CARS) microscopy. Photo-induced hydrolysis of polymeric material in aqueous media produces two hydrophilic functional groups: acid group and alcohol group. The spectral signatures identify two of the hydrophilic polar molecules as N-phenyl-4-(phenylazo)-benzenamine (C18H15N3) and phenazine-1-carboxylic acid (C13H8N2O2). The change in hydrophilicity results in a negative refractive index change in the laser-treated areas.
Gesehen am 25.07.2018